Sustainable production of glutathione from lignocellulose-derived sugars using engineered Saccharomyces cerevisiae - Kobayashi, Jyumpei; Sasaki, Daisuke; Bamba, Takahiro; Hasunuma, Tomohisa; Kondo, Akihiko (Applied Microbiology and Biotechnology, 2019)
Glutathione has diverse physiological functions, and therefore, the demand for it has increased recently. Currently, industrial mass production of glutathione is performed from D-glucose via fermentation by the budding yeast Saccharomyces cerevisiae . However, use of D-glucose often competes with demands for various other industries, leading to high production costs. To affordably produce glutathione, we aimed to produce high amounts of glutathione from D-glucose and D-xylose, which are the main constituents of lignocellulosic biomass pre-treated with acids. Genetically engineered S. cerevisiae strains that can produce high amounts of glutathione and assimilate D-xylose were constructed and cultured in media containing D-xylose. Among these recombinant strains, a S. cerevisiae GCI ( XR / XDH / XK ) strain over-expressing γ-glutamylcysteine synthetase, glutathione synthetase, D-xylose reductase, xylitol dehydrogenase, and xylulokinase genes successfully consumed D-xylose in the medium and produced the highest amount of glutathione. When strains were grown in media containing D-glucose and D-xylose, the GCI ( XR / XDH / XK ) strain showed 4.6-fold higher volumetric glutathione production (mg/L-broth), 2.2-fold higher glutathione content (%), and 2.1-fold higher cell growth (g-cell/L-broth) than the vector control strain of YPH499 (Vector). Furthermore, when recombinant S. cerevisiae strains were grown in medium containing fermentation inhibitory materials, the GCI ( XR / XDH / XK ) strain produced 5.8- and higher volumetric glutathione, 2.6-fold higher intracellular glutathione, and 2.9-fold higher cell growth than the vector control YPH499 (Vector) strain. The gradual sugar consumption by recombinant S. cerevisiae strains in medium containing D-glucose and D-xylose leads to high yields of glutathione. These results indicate the potential for glutathione production from lignocellulosic materials.